Blends in Gravity Falls TV Series - Ermi Andriani; Rio Rini Diah Moehkardi (Universitas Gadjah Mada, 2019)
This research investigates the blending process used in Gravity Falls TV series seasons I and 2. It aims to classify blends based on the classification of blends proposed by Mattiello (2013) and interpret the meaning of blends. From the data source, there are fifty-four data considered as blends. The data are categorised in three perspectives, namely: morphotactic, morphonological and graphical, and morphosemantic. The result shows that morphotactically, the most frequently used pattern is partial blend particularly the blends consist of full word followed by splinter with 49 percent data. Then, morphonologically and graphically, non-overlapping type in which neither the graphs nor the sounds of source words are overlapped each other is commonly used in the series with 57 percent of overall data. Finally, morphosemantically, the most used structure with percentage of 63 percent is right headed blend in which the head is the second source word.